Leader-Following Consensus of Multiple Uncertain Euler-Lagrange Systems Subject to Communication Delays and Switching Networks - Lu, Maobin; Liu, Lu (IEEE transactions on automatic control, 2018)
This technical note focuses on the leader-following consensus problem of multiple uncertain Euler-Lagrange systems subject to communication delays and switching networks. By integrating the feedforward control approach with the adaptive control approach, a new adaptive distributed controller is developed. As opposed to the existing literature, our result has its distinct advantages in that it can accommodate arbitrarily bounded nonuniform time-varying communication delays, and directed jointly connected switching communication networks. The effectiveness of the main result is demonstrated by some exemplary applications to cooperative control of some practical multiple mechanical systems.